Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T18:35:15+02:00
B)-x+4>-3x+3
2x>-1
x>-0,5

c)10x-15-6x≥12x-9
-8x≥6
8x≤-6
x≤-0,75

d)-0,2(5x-3) ≤ x-0,1
-x+0,6≤x-0,1
-2x≤-0,7
2x≥0,7
x≥0,35
2010-04-15T18:39:41+02:00
B) -x+4 > -3(x-1)
-x+4 > -3x+3
-x+3x > 3-4
2x > -1 \ :2
x > -1/2
c) 5(2x-3)-6x ≥ 3(4x-3)
10x-15-6x ≥ 12x-9
10x-6x-12x ≥ 15-9
-8x ≥ 6 \ :-8
x ≤ -6/8
x ≤ -3/4
d) -0,2(5x-3) ≤ x-0,1
-x+0,6 ≤ x-0,1
-x-x ≤ -0,6-0,1
-2x ≤ -0,7 \ :-2
x ≥ 0,35
2010-04-15T19:08:34+02:00
B) -x+4 > -3(x-1)
-x+4>-3x+3
-x+3x>-4+3
2x>-1/:2
x>-1/2

c) 5(2x-3)-6x ≥ 3(4x-3)
10x-15-6x ≥ 12x-9
10x-6x-12x ≥ 15-9
-8x ≥ 6/:(-8)
x ≤ -6/8

d) -0,2(5x-3) ≤ x-0,1
-x+0,6 ≤ x-0,1
0,6+0,1 ≤ x+x
0,7 ≤ 2x /:2
0,35 ≤ x

LUB

d) -0,2(5x-3) ≤ x-0,1
-x+0,6 ≤ x-0,1
-x-x ≤ -0,6 - 0,1
-2x ≤ -0,7/:(-2)
x ≥ 0,35

:)